Kinetic analysis of lower body resistance training exercises - Fauth, M.; Garceau, L.; Lutsch, B.; Gray, A.; Szalkowski, C.; Wurm, B.; Ebben, W. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study evaluated and compared the peak vertical ground reaction force (GRF) and rate of force development (RFD) for the eccentric and concentric phases of 4 lower body resistance training exercises, including the back squat, deadlift, step-up, and forward lunge. Sixteen women performed 2 repetitions of each of the 4 exercises at a 6 repetition maximum load. Kinetic data were acquired using a force platform. A repeated measures ANOVA was used to evaluate the differences in GRF between the exercises. Results revealed significant main effects for GRF both the eccentric (p = 0.001) and concentric (p = 0.001) phases. Significant main effects were also found for RFD for the eccentric (p = 0.001) and concentric phases (p = 0.001). Force and power requirements and osteogenic potential differ between these resistance training exercises.